(untitled) (Economics and region, 2021)
The article specifies the peculiarities of the organization of accounting of fixed assets at enterprises taking into account modern conditions of management. The definition of the group "fixed assets" is given. The main regulations governing the accounting of fixed assets, accounting classification of fixed assets and accounts for their accounting are considered. The main purpose of the commercial enterprise is to increase revenues and profit. This process involves fixed assets, since they produce material benefits. The article presents the concept of "basic means" in accordance with the regulatory framework. The analytical appearance of the main effects, which is created for the skin object on special cards of the appearance of the main effects, has been completed. There is no copy of the forms of the primary documentation, as if it were a vicarist’s enterprise. Analyzed ways to get to the company. At the enterprise operations are investigated, the following are taken into account: operations on receipt of fixed assets; incurring costs in connection with the acquisition; modernization and repair costs; revaluation of fixed assets; disposal of assets. It is examined what forms of documentation are used to display operations with them. The total is broken up, which is rational organization of the appearance of the main benefits of the sector of the agricultural state, and on the butt of the partnership with the fringed branch "Renaissance", to ensure the most effective way of winning. This will lead to an increase in agricultural production, which will increase the number of food products that will meet the needs of the population.